1988
DOI: 10.1007/bf00702872
|View full text |Cite
|
Sign up to set email alerts
|

Siblings with chromosome mosaicism, microcephaly, and growth retardation: the phenotypic expression of a human mitotic mutant?

Abstract: We report male and female siblings with extreme microcephaly and mental retardation, growth retardation, and multiple chromosome mosaicism. Mental retardation associated with chromosome mosaicism does not always carry a low recurrence risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Since the multiple congenital anomalies/mental retardation syndrome associated with this cytogenetic phenomenon was first reported by Scheres et al (1986), to date, only several patients have been reported (Tolmie et al 1988;Papi et al 1989;Miller et al 1990;Warburton et al 1991;Limwongse et al 1997;Nash et al 1997;Flejter et al 1998;Kajii et al 1998). Clinical features in the reported patients were variable, but growth retardation and microcephaly were frequently described.…”
Section: Introductionmentioning
confidence: 96%
“…Since the multiple congenital anomalies/mental retardation syndrome associated with this cytogenetic phenomenon was first reported by Scheres et al (1986), to date, only several patients have been reported (Tolmie et al 1988;Papi et al 1989;Miller et al 1990;Warburton et al 1991;Limwongse et al 1997;Nash et al 1997;Flejter et al 1998;Kajii et al 1998). Clinical features in the reported patients were variable, but growth retardation and microcephaly were frequently described.…”
Section: Introductionmentioning
confidence: 96%
“…The term mosaic variegated aneuploidy was first proposed by Vigfusson et al [1986] to describe the cytogenetic finding in macaque monkey. Only 10 human cases have been reported, all ascertained because of phenotypic abnormalities [Bitoun et al, 1994;Issa et al, 1996;Miller et al, 1990;Papi et al, 1989;Scheres et al, 1986;Tolmie et al, 1988;Warburton et al, 1991]. Warburton et al [1991] proposed the use of a term mosaic variegated aneuploidy with microcephaly in these patients, as microcephaly was the most consistent phenotypic abnormality in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are differences: no multibranched configurations were found in our patient, and PCD was not restricted to specific chromosomes; moreover, in the ICF syndrome, no aneuploidies or C-anaphase-like structures have been reported. Tolmie et al (1988) described retarded and microcephalic siblings with chromosome mosaicism mainly concerning trisomy 18; the expression of a mitotic mutant was suspected. A similar observation has been reported by Papi et al (1989).…”
Section: Discussionmentioning
confidence: 99%